VD_FINDINFO Jug / 2023 / 422 vom 10. Oktober 2022 - VD Tribunal cantonal (2022)
FIXATION DE LA PEINE, EXPULSIONDROIT PÉNAL, CONCOURS D'INFRACTIONS, ESCROQUERIE | 146 al. 1 CP, 47 CP, 49 al. 1 CP, 66a al. 1 let. o CP, 66a al. 2 CP